Youth, Emotional Energy, and Political Violence: The Cases of Egypt and Saudi Arabia Survey, 2005 - Moaddel, Mansoor ([Verlag nicht ermittelbar], 2010)
The purpose of the current study was to explore and understand the values, the general opinions, and the sociopolitical and cultural attitudes of youths in Egypt and Saudi Arabia. The researchers conducted face-to-face interviews of youths in six selected cities, three in Egypt and three in Saudi Arabia. The researchers explained to the youths what they were studying and followed by asking them a variety of different social issue questions dealing with religion, marriage, political systems, employment, freedom, and economic development. They also gathered demographic data such as age, education, race, religion, and socio-economic status from those interviewed. The dataset contains a total of 224 variables pertaining to the general opinion of youths in regards to a variety of social issues. Also included are demographic variables.